PENGARUH KOMPETENSI GURU DAN IKLIM ORGANISASI TERHADAP KINERJA GURU PENDIDIKAN AGAMA ISLAM SEKOLAH DASAR DI KECAMATAN GUNUNG TALANG KABUPATEN SOLOK - Rahmi Fitria (IAIN Batusangkar, 2016)
Effect of Teacher Competence and Organizational Climate on Performance of Islamic Education teachers elementary school in District of Gunung Talang in Solok regency. Issues raised in this study is the effect of teacher competence and school organizational climate on the performance of Islamic religious education teachers at the elementary school in the district of Gunung Talang in Solok regency. This study aims to determine the effect of teacher competence and organisasisekolah climate on the performance of Islamic religious education teacher elementary school in the district of Gunung Talang in Solok regencyThe results of heypothesis testing showed that: (1) there is a positive dan significant impact competence of teachers on teacher performance of Islamic Education Elementary School 0f 31.4% and (2) there is a positive dan significant impact school organizational climate on the teachers performance of Islamic Education Elementary School of 48.8% (3) ) there is a positive dan significant impact competence of teachers and school organizational climate jointly on the teachers performance of Islamic Education Elementary School of 55.9%Kata Kunci: Kinerja, kompetensi, iklim organisasi